Welding fundamentals - Roger W Jellison (Prentice-Hall, 1996)
The book will meet the requirements of those individuals who need to acquire welding skills in order to improve their career opportunities. It addresses the training needs using a hand-on approach. This book will present essential technical information for class discussions of welding safety, power sources, blueprint reading, inspection methods, and other pertinent topics. The many tables and figures are designed to present conveniently data. The topics of discussion are illustrated with several chapter highlight real-world examples that include stories about how welding techniques are used efficiently